2008
DOI: 10.3399/bjgp08x279689
|View full text |Cite
|
Sign up to set email alerts
|

Using vital signs to assess children with acute infections: a survey of current practice

Abstract: GPs are advised to measure vital signs in children presenting with acute infections. Current evidence supports the value of GPs' overall assessment in determining how unwell a child is, but the additional benefit of measuring vital signs is not known. AimTo describe the vital signs and clinical features that GPs use to assess children (aged <5 years) with acute infections. Design of studyQuestionnaire survey. SettingAll 210 GP principals working within a 10 mile radius of Oxford, UK. MethodData were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 17 publications
0
28
1
Order By: Relevance
“…Part of this fear has been induced by doctors themselves, who also try to stay on the safe side. 9 How to avoid missing serious infection in children in general practice is an ongoing subject of research and debate, 22,23 but guidelines that advocate the use of more biomedical measures by GPs, such as heart rate or capillary refill time, can affect the way parents manage their sick children, as these measures might also become generally accepted for use at home. Doctors should realise the long-term effects of their actions on the attitudes of parents.…”
Section: Implications For Future Research and Clinical Practicementioning
confidence: 99%
“…Part of this fear has been induced by doctors themselves, who also try to stay on the safe side. 9 How to avoid missing serious infection in children in general practice is an ongoing subject of research and debate, 22,23 but guidelines that advocate the use of more biomedical measures by GPs, such as heart rate or capillary refill time, can affect the way parents manage their sick children, as these measures might also become generally accepted for use at home. Doctors should realise the long-term effects of their actions on the attitudes of parents.…”
Section: Implications For Future Research and Clinical Practicementioning
confidence: 99%
“…A recent survey of GPs revealed a minority (9%) reported they used a pulse oximeter to measure pulse rate, or to assess respiratory status (20%). 4 In clinical examination, a traditional sign of hypoxia is central cyanosis. However, studies have shown clinicians have difficulty in reliably detecting hypoxaemia until the saturation is <80%.…”
Section: Previous Researchmentioning
confidence: 99%
“…Possible explanations for this discrepancy in performance of CPRs at the GPC and ED, may be that in the primary care setting observed frequencies of CPR variables are low, vital signs are barely measured, 34 and additional diagnostic tests, such as inflammatory markers, are unavailable. These issues reduced the heterogeneity of CPR variable outcomes, and thus of the predicted risks for each patient in the GPC population (that is, less spread of the predicted risks).…”
Section: Discuss This Articlementioning
confidence: 99%